Influence of spectral interferences on the results of quartz determination by infrared spectrometry - Aleksandra Maciejewska (Nofer Institute of Occupational Medicine, 2015)
Background: Determination of quartz by Fourier transform infrared spectrometry (FTIR) is not specific: the obtained results are influenced by matrix components, some of which cause spectral interference. The aim of the study was to evaluate the effect of dust components responsible for spectral interference with quartz on the results of its determinations, and to develop methods to minimize the effects of interferences. Material and Methods: Investigation of interferent effects were conducted using respirable dusts: quartz SRM 1878a, cristobalite SRM 1879a, synthetic amorphous silica (Zeosil) and feldspar, albite and kaolinite. For the study 17 mixtures with quartz and interferents at concentrations from 10 to 90% were prepared. Determinations of quartz were carried out by the KBr disc method. Results: In mixtures of quartz with interferents, the results based on bands 798-779 cm-1 were overestimated by 10-55%, while those based on band 695 cm-1 were closer to the true content of quartz. It was found that the best methods able to decrease the impact of spectral interference are: scaled subtraction of IR spectra of feldspar or kaolinite analysed in nonashed samples, correction curve for kaolinite also investigated in nonashed samples with quartz-content calculation based on band 695 cm-1 in mixtures with cristobalite, amorphous silica or kaolinite in ashed samples. Conclusions: The study indicates the need to identify spectral interferences in dust when determining crystalline silica by FT-IR and to take actions to minimize their impact on the obtained results. Med Pr 2015;66(4):497-509